Studies on essential oils. Part 35: chemical and biocidal investigations on Tagetes erecta leaf volatile oil - Singh, Gurdip (2003)
Chemical investigations on the leaf essential oil of Tagetes erecta, performed by HPLC, GC and GC–MS techniques, showed the presence of 26 components, accounting for 89% of the total oil. The major constituents were (Z)-ˇ-ocimene (42.2%), dihydrotagetone (14.3%), (Z)-tagetone (8.3%), limonene (7.3%), (E)-ocimenone (6.1%) and (Z)-ocimenone (5.3%). The biocidal investigations showed that the oil possessed a significant but limited and dose-related antifungal and insecticidal activity. The oil showed 100% mortality of white termite (Odontotermes obesus Rhamb.) at a dose of 6 µl/Petri-plate after 24 h of exposure, while at lower doses and shorter exposures it showed diminished mortality rates. The oil only partially affected the mycelial growth of any of the tested fungi. Thus, the leaf oil of this plant, which is rich in (Z)-ˇ-ocimene, has a statistically significant antifungal and insecticidal activity.